STRATEGI PENGELOLAAN KERAMBA JARING APUNG BERKELANJUTAN DI WADUK KEDUNGOMBO, JAWA TENGAH - Iwan Chandra Binsar Hamonangan Simanjuntak (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
A study on the strategy of the management of sustainable floating-net cage fisheries in the Kedungombo Reservoir, Central Java was conducted on MayJuly 2018. Based on the carrying capacity, the number of FNC units currenly in the reservoir during the period study is 3781 units. This amount has exceeded the carrying capacity of the FNC in the resevoir which is 1025 units. This shows that FNC must be managed so that fish culture in floating net cages in the reservoir is sustainable. This study aims to determine the FNC management strategy in the Kedungombo Reservoir. The samples were taken using purposivesampling method. Data collection in this research consist of primary data taken from interview and analyzed using SWOT analysis method and secondary data obtained from the Department of Fisheries and Animal Husbandry, Sragen Regency. The result of the research through descriptive SWOT analysis show that matrix value of internal factor at 1.05 while matrix value of external factor at 1.55, with the implementation of the SO (Strength-Opportunity) strategy. Fish farming in floating net cages in Kedungombo Reservoir has the opportunity and strength so that it can take advantage of existing opportunities by minimazing threats and weaknesses.Keywords: Floating Net Cages, Kedungombo Reservoir, strategy.